Environmental enrichment blocks reinstatement of ethanol-induced conditioned place preference in mice. (10th July 2015) - Li, Xinjuan; Meng, Li; Huang, Keyu; Wang, Hua; Li, Dongliang
Highlights: The effect of training dose on the extinction of ethanol-induced CPP was investigated in mice. The effect of training dose on the relapse of ethanol-induced CPP was investigated in mice. Environmental enrichment blocked the reinstatement of ethanol-induced CPP. Environmental enrichment did not affect the extinction rate of ethanol-induced CPP. Abstract: This study aimed to explore the effect of environmental enrichment (EE) on the reinstatement of ethanol-induced conditioned place preference (CPP) in C57Bl/6J mice. To investigate the effect of training dose on the extinction and relapse of ethanol-induced CPP, doses of ethanol were applied and we found 0.8 g/kg and 1.6 g/kg training doses lead to significant CPP. In the reinstatement procedure, previously extinguished 1.6 g/kg ethanol CPP could be markedly reinstated by a priming injection of 0.8 g/kg. In contrast, priming with 0.4 g/kg of ethanol failed to reinstate the CPP induced by 0.8 g/kg. To investigate whether concomitant EE exposure could prevent the reinstatement of ethanol-induced CPP, one half of the mice were housed in standard environment (SE) and the other half in EE during the extinction and reinstatement session in the second experiment. Our study showed that reinstatement of ethanol-induced CPP was blocked by EE and the extinction rate was the same between SE and EE mice. These findings suggest that EE can block reinstatement of ethanol-induced CPP in mice, and aiding in the identification of new therapeutic strategies for alcohol addiction.